Repression of Lateral Organ Boundary Genes by PENNYWISE and POUND-FOOLISH Is Essential for Meristem Maintenance and Flowering in Arabidopsis. Issue 3 (28th September 2015) - Khan, Madiha; Ragni, Laura; Tabb, Paul; Salasini, Brenda C.; Chatfield, Steven; Datla, Raju; Lock, John; Kuai, Xiahezi; Després, Charles; Proveniers, Marcel; Yongguo, Cao; Xiang, Daoquan; et al.
Abstract : Two homeobox domain proteins maintain meristem activity essential for flowering by repressing an organ boundary gene module. Abstract: In the model plant Arabidopsis ( Arabidopsis thaliana ), endogenous and environmental signals acting on the shoot apical meristem cause acquisition of inflorescence meristem fate. This results in changed patterns of aerial development seen as the transition from making leaves to the production of flowers separated by elongated internodes. Two related BEL1-like homeobox genes, PENNYWISE ( PNY ) and POUND-FOOLISH ( PNF ), fulfill this transition. Loss of function of these genes impairs stem cell maintenance and blocks internode elongation and flowering. We show here that pny pnf apices misexpress lateral organ boundary genes BLADE-ON-PETIOLE1/2 ( BOP1/2 ) and KNOTTED-LIKE FROM ARABIDOPSIS THALIANA6 ( KNAT6 ) together with ARABIDOPSIS THALIANA HOMEOBOX GENE1 ( ATH1 ). Inactivation of genes in this module fully rescues pny pnf defects. We further show that BOP1 directly activates ATH1, whereas activation of KNAT6 is indirect. The pny pnf restoration correlates with renewed accumulation of transcripts conferring floral meristem identity, including FD, SQUAMOSA PROMOTER-BINDING PROTEIN LIKE genes, LEAFY, and APETALA1 . To gain insight into how this module blocks flowering, we analyzed the transcriptome of BOP1 -overexpressing plants. Our data suggest a central role for the microRNA156-SQUAMOSA PROMOTER BINDING PROTEIN-LIKE-microRNA172 module in integrating stress signals conferred in part by promotion of jasmonic acid biosynthesis. These data reveal a potential mechanism by which repression of lateral organ boundary genes by PNY-PNF is essential for flowering.